Marginal Microleakage of Conventional Fissure Sealants and Self-Adhering Flowable Composite as Fissure Sealant in Permanent Teeth - Rahimian-Imam, Sara (J Dent (Tehran), 2015)
OBJECTIVES: Application of sealants is a safe and effective way to prevent occlusal caries in the posterior teeth. A successful sealant therapy depends on good isolation. Decreased steps of adhesive application may enable proper isolation and use of self-adhering flowable composites for sealant therapy. This study sought to compare the marginal microleakage of fissure sealants and self-adhering flowable composites in permanent teeth. MATERIALS AND METHODS: This in vitro, experimental study was conducted on 60 extracted human premolar teeth. The teeth were divided randomly into two groups of 30. In the first group, fissure sealant (Clinpro, 3M ESPE, USA) was placed on the teeth. In the second group, self-adhering flowable composite (Vertise Flow, Kerr, USA) was applied as the sealant. Then, both groups were immersed in 0.5% fuchsin dye solution for 24 hours. Sectioned samples were observed with a stereomicroscope for the extent of dye penetration. Data were analyzed using SPSS 21 and the Mann-Whitney test (P<0.05). RESULTS: Microleakage in the fissure sealant group was significantly higher than that in the self-adhering flowable composite group (P<0.001). CONCLUSION: Microleakage was less using self-adhering flowable composite compared to conventional fissure sealant; therefore, self-adhering flowable composite can be used as a suitable fissure sealant in permanent teeth.